Analysis of Labor Absorption in Small Industries in Palangka Raya City (Case Study in Pahandut, Jekan Raya and Sabangau Districts) - Miar Miar; Ahmad Rizani; Desi Desi (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2021)
The purpose of this study was to analyze the effect of capital, labor productivity and labor wages in the labor absorption on small industries in Palangka Raya City partially or simultan. This type of study was quantitative study by conducting interviews and questionnaires to 100 respondents of small industry entrepreneurs in Palangka Raya City ( Case studies in the sub-districts of Pahandut, Jekan Raya and Sabangau) by using multiple linear regression analysis tool. The results of this study showed that simultaneously capital, labor productivity and labor wages have a significant effect on employment. Partially capital, labor productivity and labor wages have a significant effect on labor absorption